Effects of Taurine on Primary Metabolism and Transcription in a Coral Symbiodinium sp. - Huang, Aiyou; Shi, Hejing; Cui, Ruoxuan; Cai, Xiaoni; Xie, Zhenyu (Frontiers in Microbiology, 2022)
Coral reefs are marine ecosystems that host the richest biodiversity of marine organisms. Coral reefs are formed as a result of the symbiotic relationship between the host coral animal and photosynthetic dinoflagellates namely zooxanthellae. Coral animals control the direction of carbon fixation products of symbiotic zooxanthellae through the secretion of host release factors (HRFs) such as taurine. To study the potential effect of taurine on photosynthesis and the direction of carbon fixation products of zooxanthellae, we compared the growth of zooxanthellae under control and taurine-stimulated conditions. Metabolome and transcriptome analyses were performed to analyze the potential effect of taurine on primary metabolism and mRNA transcription. The results revealed that taurine significantly increased the growth and free amino acid content of Symbiodinium sp. Results of metabolome and transcriptome analyses suggested that taurine might affect metabolic pathways in zooxanthellae by altering the permeability of the algal cell membrane, diverting photosynthetically fixed carbon from storage compounds to translocated compounds, releasing low concentrations of nitrogen to initiate a series of response mechanisms, and controlling the density of zooxanthellae through the quorum sensing effect. We expected to explore how corals control carbon metabolism in zooxanthellae and to provide theoretical guidance for furthering our understanding of zooxanthellae biology and coral-algal symbiosis.